Pelatihan Penyusunan Laporan Keuangan Sesuai Standar Akuntansi Keuangan Entitas Privat Bagi Musyawarah Guru Mata Pelajaran Akuntansi Jakarta Pusat - Auliffi Ermian Challen; Elmanizar Elmanizar; Sovi Ismawati Rahayu; Yenny Akmalia (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The implementation of FAS for Private Entities replacing FAS for Non Publicly Accountable Entities shows the development of accounting standards. The development of these standards is expected to be followed by an increase in the understanding of teachers who have a role in the education of vocational students, especially accounting majors. This service activity aims to help the Central Jakarta Accounting MGMP provide training in preparing company financial statements according to FAS for Private Entity for MGMP teachers. The training is carried out in a hybrid manner, namely face-to-face and online. The training method is carried out using lectures, demonstrations, discussions, and question and answer methods. The activity participants were teachers who were members of the Accounting MGMP from public and private vocational schools in Central Jakarta in both Regions I and II. The number of participants who attended face-to-face amounted to 50 people and 44 participants who attended online. Based on the results of the participant evaluation, the teachers gained an increased understanding of the preparation of company financial statements in accordance with FAS for Private Entities and will implement it in the teaching process at school.